Overconfidence, Trading frequency, and Portfolio Size in the Egyptian Stock Market - Aziz, Wessam M. Abdel; Ismail, Elsayeda A.; El-Hennawi, Mohamed S. (IJRDO - Journal of Business Management, 2016)
Using daily trading records data of 744 adult Egyptian Individual investors; acquired from Misr for Central Clearing, Depository and Registry (hereafter, M.C.D.R); we investigate whether the Egyptian individual investors exhibit overconfidence in their investment decisions. In addition, we delineate the effect of overconfidence on trading frequency and portfolio size. The results of our analysis reveal that: There is an over whelming evidence that the Egyptian Investors display overconfidence in their trade. However, investors exhibiting overconfidence don’t trade more frequently. In addition, overconfident investors tend to hold small size portfolios.